Analysis of Teachers' Problems in Learning the Quran - Guslianto, Guslianto; Pasaleron, Roni; Burhanuddin, Burhanuddin; Rahman, Ikhwan; Oktavia, Gifa (Al-kayyis: Journal of Islamic Education, 2024)
The Koran is the holy book of Muslims, a guide and instruction in life for the Muslim community. A hadith says “The best of you are those who learn the Qur'an and teach it”. Someone who is said to be successful in anything is due to the encouragement and assistance of a teacher who teaches it, but in this study will discuss the problematics of teachers in learning the Qur'an. This study aims to analyze i). Profile of the Koran teacher in a village ii). What methods are used by Koran teachers in teaching it iii). problems faced by Koran teachers. This research uses a qualitative method with a case study approach. Data sources were taken from four informants through in-depth interviews. All informants are Koran teachers in a village. The results showed that the profile of the Koran teacher has not met the requirements as a Koran teacher, because some of them do not have an educational background according to the department they are teaching now. The methods used by Koran teachers to teach are recitation, tartil and iqro' methods. Problems faced by the Koran teacher are: i). Inadequate facilities and infrastructure, ii). Teachers do not get a salary or intensive from the government, iii). Lack of teacher competence as a Koran teacher, iv). Koran teachers do not attend Koran teacher training from the government, v). The lack of government attention to the places and welfare of Koran teachers. vi). Lack of attention from student guardians to their children's Koran education.